2009
DOI: 10.1002/esp.1818
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the SWEEP model during high winds on the Columbia Plateau

Abstract: A standalone version of the Wind Erosion Prediction System (WEPS) erosion submodel, the Single-event Wind Erosion Evaluation Program (SWEEP), was released in 2007. A limited number of studies exist that have evaluated SWEEP in simulating soil loss subject to different tillage systems under high winds. The objective of this study was to test SWEEP under contrasting tillage systems employed during the summer fallow phase of a winter wheat-summer fallow rotation within eastern Washington. Soil and PM10 (particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Similarly, soil loss during the 17 and 23 Oct. 2003 erosion event (44 kg ha -1 ) may have been lower than the 9 Sept. 2005 event because of differences in aggregate geometric mean diameter. Although the data of Sharratt et al (2015) indicated that differences in random roughness (10 versus 9 mm) and residue cover (3 versus 11%) could not account for differences in soil loss between the 17 and 23 Oct. 2003 and 9 Sept. 2005 erosion events, the geometric mean diameter was 1.4 mm for the 17 and 23 Oct. 2003 event (Feng and Sharratt, 2007) and 0.4 mm for the 9 Sept. 2005 event (Feng and Sharratt, 2009). In contrast to observed soil loss across erosion events, Schillinger and Papendick (2008) estimated a loss approaching 180 Mg ha -1 during a single erosion event in the region.…”
Section: Loss Of Soil Cmentioning
confidence: 88%
“…Similarly, soil loss during the 17 and 23 Oct. 2003 erosion event (44 kg ha -1 ) may have been lower than the 9 Sept. 2005 event because of differences in aggregate geometric mean diameter. Although the data of Sharratt et al (2015) indicated that differences in random roughness (10 versus 9 mm) and residue cover (3 versus 11%) could not account for differences in soil loss between the 17 and 23 Oct. 2003 and 9 Sept. 2005 erosion events, the geometric mean diameter was 1.4 mm for the 17 and 23 Oct. 2003 event (Feng and Sharratt, 2007) and 0.4 mm for the 9 Sept. 2005 event (Feng and Sharratt, 2009). In contrast to observed soil loss across erosion events, Schillinger and Papendick (2008) estimated a loss approaching 180 Mg ha -1 during a single erosion event in the region.…”
Section: Loss Of Soil Cmentioning
confidence: 88%
“…It is critical in these comparisons to note that all of the studies referenced above were from agricultural fields, many of them were bare, and on which soil parameters could be measured in detail. All of the studies cited above except Feng and Sharratt [] were also for individual storms. Bare soil or homogenous crop plantings and single events with on‐site meteorological measurements are arguably much simpler systems for modeling aeolian transport than the structurally and spatially heterogeneous rangelands used in this study.…”
Section: Discussionmentioning
confidence: 98%
“…All of the studies cited above except Feng and Sharratt [2009] were also for individual storms. Bare soil or homogenous crop plantings and single events with on-site meteorological measurements are arguably much simpler systems for modeling aeolian transport than the structurally and spatially heterogeneous rangelands used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…SWEEP requires input of 38 parameters (as described in Feng and Sharratt, 2009) that define crop and residue characteristics (e.g., growing and dead crop leaf area index and residue flat cover), soil properties (e.g., geometric mean diameter of aggregate size and surface water content), and weather characteristics (e.g., wind direction and wind speed). The SWEEP model simulates soil loss (in terms of total, creep + saltation, suspension, and PM-10 emission) for site-specific, planned surface conditions and control practices for a given day of the year.…”
Section: Methodsmentioning
confidence: 99%
“…Total amounts crossing each cell boundary are also provided. Similar to WEPS, the SWEEP model has been extensively validated in both the United States and internationally (e.g., Feng and Sharratt, 2009; Liu et al, 2014; Pi et al, 2014a; Pi et al, 2014b; Pi et al, 2016) and has been shown to perform well across a wide range of soils and cropping systems.…”
Section: Methodsmentioning
confidence: 99%